The potential of oil palm waste as source of glucose and their applications towards bioethanol and animal feedstock: a review / Mohamad Syahril Hafiz Radzali - Radzali, Mohamad Syahril Hafiz (Faculty of Plantation and Agrotechnology, 2017)
Malaysia currently is the world’s largest producer and exporter of oil palm product. Besides producing oil and fat, there is a continuous increasing in interest of regarding to generate oil palm waste as a biomass product. Basically oil palm biomass product consist of oil palm trunk, empty fruit bunch, oil palm frond, and etc. Oil palm trunk is one of the material use to produce biomass product because it highly rich in palm sap that can be generated glucose. Based on numerous studies has shown that glucose have a huge of potential such as feedstock for food security and generated renewable energy source. This paper will discuss the variation of glucose production and their approach by using hydrolysis process, and fermentation process to extract the potential of glucose. Based on the reviews it can be concluded clearly Malaysia has huge potential to generate and utilize biomass energy as a source of renewable energy. In order to reduce the abundant of palm waste, it can be convert into animal feedstock like silage, pellet, cube, and etc. This will lead Malaysia to be a role model as example to other countries in the world to manage their abundant of agriculture waste.